SH2B3, Transcribed by STAT1, Promotes Glioblastoma Progression Through Transducing IL-6/gp130 Signaling to Activate STAT3 Signaling - Cai, Shan; Lu, Jian-xiang; Wang, Yan-pei; Shi, Chao-jia; Yuan, Tian; Wang, Xiang-peng (Frontiers in Cell and Developmental Biology, 2021)
Glioblastoma (GBM) is the most common and aggressive brain tumor in adults. The aberrant activation of STAT3 commonly occurs in GBM and is a key player in GBM tumorigenesis. Yet, the aberrant activation of STAT3 signaling is not fully understood. Here, we report that SH2B adaptor protein 3 (SH2B3) is highly expressed in GBM and preferentially expressed in GBM stem cells (GSCs). Moreover, SH2B3 high expression predicts worse survival of GBM patients. Targeting SH2B3 considerably impairs GBM cell proliferation, migration, and GSCs’ self-renewal in vitro as well as xenograft tumors growth in vivo. Additionally, we provide evidence suggesting that STAT1 directly binds to the promoter of SH2B3 and activates SH2B3 expression in the transcriptional level. Functionally, SH2B3 facilitates GBM progression via physically interacting with gp130 and acting as an adaptor protein to transduce IL-6/gp130/STAT3 signaling. Together, our work firstly uncovers that the STAT1/SH2B3/gp130/STAT3 signaling axis plays critical roles in promoting GBM progression and provides insight into new prognosis marker and therapeutic target in GBM.